2021
DOI: 10.1186/s12936-021-04010-8
|View full text |Cite
|
Sign up to set email alerts
|

Neglected malaria parasites in hard-to-reach areas of Odisha, India: implications in elimination programme

Abstract: Background Information on the foci of Plasmodium species infections is essential for any country heading towards elimination. Odisha, one of the malaria-endemic states of India is targeting elimination of malaria by 2030. To support decision-making regarding targeted intervention, the distribution of Plasmodium species infections was investigated in hard-to-reach areas where a special malaria elimination drive, namely Durgama Anchalare Malaria Nirakaran (DAMaN) began in 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Among category-3 states/UTs, Odisha showed the highest mean number of malaria cases for the years 2017-2021, due to many reasons, including the wide distribution of Plasmodium ovale and Plasmodium malariae in different geophysical regions of the state ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among category-3 states/UTs, Odisha showed the highest mean number of malaria cases for the years 2017-2021, due to many reasons, including the wide distribution of Plasmodium ovale and Plasmodium malariae in different geophysical regions of the state ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Odisha, an eastern Indian state with 4% of the total population contributes almost 40% of the annual malaria burden of the country, mostly reported from hilly forested areas inhabited by the tribal population, the majority of them are due to P. falciparum and P. vivax [5,16]. Although separate studies have reported the prevalence of sickle cell, G6PD deficiency, and malaria in tribaldominated areas of the state [17][18][19][20][21], but PVTGs-specific comprehensive data on these genetic disorders and their association with malaria are lacking, which is a pre-requisite for the institution of a cost-effective screening system as well as an intervention program. Earlier the Expert Committee on Tribal Health (2013) jointly constituted by the Ministry of Tribal Affairs and Ministry of Health and Family Welfare, Government of India and NITI Ayog, India (2018) have emphasised on generating information on important health issues such as sickle cell and malaria of these vulnerable population so as to achieve the UN Sustainable Development Goals (SDG) [22].…”
Section: Introductionmentioning
confidence: 99%